Digital Financial Bookkeeping Training for MSME Entrepreneurs - Damayanti, Misvia; Putra, Purnama; Khoiriyah , Ummi; Widyowati, Dian Desty (Entrepreneurship and Community Development, 2024)
The service activity aims to provide outreach, training, and assistance to MSMEs in Sukabungah Village on creating digital financial bookkeeping. Effective bookkeeping is crucial for business progress, enabling MSMEs to track financial flows, income, and profits accurately. Observations reveal that while MSME actors in Sukabungah Village engage in bookkeeping, it is not performed optimally. To address this, the service team implemented a digital bookkeeping training program using the "BukuWarung" application. The program's results demonstrate significant improvements in the financial management and bookkeeping capabilities of MSME actors. Participants reported increased knowledge and understanding of financial transactions within their businesses and the ability to classify these transactions into assets, liabilities, income, and expenses. They learned to execute an entire accounting cycle, including recording financial transactions in journal form, posting to the ledger, preparing trial balances, and generating profit and loss statements and financial position reports. Overall, the training program has enabled MSMEs in Sukabungah Village to manage their finances more effectively, contributing to business progress and enhancing the welfare of both MSME actors and the broader community.